Lung Ultrasonography for the Diagnosis of Pleural Effusion in Children - Ayuningtyas, Dewi Sitoresmi; Martuti, Sri; Riza, Muhammad (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background:Chest radiograph was currently the standard imaging for diagnosing pleural effusion. However, there were many limitations, namely radiation, varying interpretation, and long time to get results. Lung ultrasonography is an alternative procedure that is easy to learn and offers many benefits, including noninvasive, ra